2021
DOI: 10.1002/pa.2763
|View full text |Cite
|
Sign up to set email alerts
|

Has knowledge improved economic growth? Evidence from Nigeria and South Africa

Abstract: This study examines whether knowledge causes economic growth in Africa's two leading economies: Nigeria and South Africa. Using the Vector Autoregressive and Vector Error Correction approach, the findings show cointegration among the variables. The speed of convergence of the variables to their long-term mean values is relatively higher for South Africa than for Nigeria. In the short run, it is observed that knowledge unidirectionally Granger causes growth for Nigeria, whereas bidirectional causality is observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Another reality is that 3.7% of South Africa's Gross Domestic Product (GDP) originates from the tourism sector (Chitiga et al, 2022). This is relatively low when compared to other sectors such as mining and energy processing which contributed 8.7% and investment which accounted for 13.1% in 2021 (Shobande & Asongu, 2022). Therefore, one can argue that the tourism sector in South Africa is not performing satisfactorily in terms of the economy.…”
Section: Background To Contextmentioning
confidence: 96%
“…Another reality is that 3.7% of South Africa's Gross Domestic Product (GDP) originates from the tourism sector (Chitiga et al, 2022). This is relatively low when compared to other sectors such as mining and energy processing which contributed 8.7% and investment which accounted for 13.1% in 2021 (Shobande & Asongu, 2022). Therefore, one can argue that the tourism sector in South Africa is not performing satisfactorily in terms of the economy.…”
Section: Background To Contextmentioning
confidence: 96%
“…However, in past decades, experience has shown that most FDI inflows to Nigeria have been delayed or prolonged. In fact, several investors have pulled out their funds from the domestic market owing to the poor nature of the economy (Onyeukwu 2007;Onyeiwu and Shrestha 2004;Shobande and Asongu 2021). Secondly, Nigeria is the most favoured and third host economy in Africa, with a teeming population and large market size, driving demand for foreign-made goods.…”
Section: Introductionmentioning
confidence: 99%